Seychelles : First Review Under the Extended Arrangement, Request for Modification of Performance Criteria, and Financing Assurances Review; Staff Report; Staff Supplement; and Press Release. (IMF Staff Country Reports; Country Report, 2010)
The fiscal policy stance continues to be appropriate, facilitating a reduction in public debt. Seychelles has made a good start on its second stage of reforms under an Extended Fund Facility (EFF)-supported program, despite a difficult international environment, showing strong resilience to the double crisis it confronted. The economy is reaping the benefits of strong macroeconomic stabilization policies. Seychelles remains highly exposed to external shocks. Progress on the ambitious program of tax and public finance management reform is encouraging, but important steps still lie ahead.